Effective removal of iron, nutrients, micropollutants, and faecal bacteria in constructed wetlands cotreating mine water and sewage treatment plant effluent - Jidapa Plaimart; Kishor Acharya; Adrian Blackburn; Wojciech Mrozik; Russell J. Davenport; David Werner (Water Science and Technology, 2024)
Regulators in England and Wales have set new targets under the Environment Act 2021 for freshwater quality by 2038 that include halving the length of rivers polluted by harmful metals from abandoned mines and reducing phosphorus loadings from treated wastewater by 80%. In this context, an intriguing win–win opportunity exists in the removal of iron from abandoned mines and phosphate from small sewage treatment plants by coprecipitation in constructed wetlands (CWs). We investigated such a CW located at Lamesley, Northeast England, which cotreats abandoned coal mine and secondary-treated sewage treatment plant effluents. We assessed the removal of nutrients, heavy metals, organic micropollutants, and faecal coliforms by the CW, and characterized changes in the water bacteriology comprehensively using environmental DNA. The CW effectively removed ammonium-nitrogen, phosphorus, iron, and faecal coliforms by an average of 86, 74, 98, and 75%, respectively, to levels below or insignificantly different from those in the receiving river. The CW also effectively removed micropollutants such as acetaminophen, caffeine, and sulpiride by 70–100%. Molecular microbiology methods showed successful conversion of sewage and mine water microbiomes into a freshwater microbiome. Overall, the CW significantly reduced impacts on the rural water environment with minimal operational requirements. HIGHLIGHTS The CW removed iron from mine water and phosphorus from wastewater by coprecipitation.; The CW effectively removed nutrients, faecal bacteria, and micropollutants.; Dissolved Cu, Zn, Mn, and total dissolved solids were not effectively removed.; The CW converted mine water and sewage microbiomes into a freshwater microbiome.; The CW simultaneously addressed wastewater and mine water pollution issues.;